2017
DOI: 10.11648/j.ijmsa.20170604.16
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the Effects of Alloying Elements on the Hardenability of Steels to the Diffusion Coefficients of Elements in Fe

Abstract: Abstract:The effects of various alloying elements on the hardenability of steels are known experimentally, but the reasons for these effects are not well understood. In this work, the upper critical cooling rate was selected as the index of hardenability. Changes in the upper critical cooling rate of steel caused by the presence of alloying elements and the diffusion coefficients of those elements in the ã-phase of Fe, plotted on thermal conductivity-Young's modulus diagrams, showed similar patterns. The corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Formerly, the author showed that the corrosion resistance of Zircaloy was provided by the precipitates in the alloy matrix through the mechanism of the anodic protection [1]. Recently, the author introduced the diagram with thermal conductivity on the abscissa and Young's modulus on the ordinate to explain the various properties of elements [2][3][4][5][6]. This diagram will be called "TC-YM diagram" or "diagram".…”
Section: Introductionmentioning
confidence: 99%
“…Formerly, the author showed that the corrosion resistance of Zircaloy was provided by the precipitates in the alloy matrix through the mechanism of the anodic protection [1]. Recently, the author introduced the diagram with thermal conductivity on the abscissa and Young's modulus on the ordinate to explain the various properties of elements [2][3][4][5][6]. This diagram will be called "TC-YM diagram" or "diagram".…”
Section: Introductionmentioning
confidence: 99%